2007
DOI: 10.1007/s11135-007-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

A meta-validation model for assessing the score-validity of student teaching evaluations

Abstract: Teaching evaluations, Formative evaluation, Summative evaluation, Meta-validity model, Meta-validity analysis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 52 publications
1
49
0
8
Order By: Relevance
“…On the one hand, it may improve the lecturer's teaching quality and, on the other hand, it may provide a wise and precise decision making tool for the administrative staff with regard to lecturers continuing employment, tenure, promotion of appointment committees and so on. Many studies have indicated strong evidence with regard to the validity and reliability of the teaching evaluation tool (Al-Saghir, 2008;Onwuegbuzie, Daniel, & Collins, 2009). On the other hand, Spooren, Brockx and Mortelmans (2013) claimed that teaching evaluation by students has thus far failed to provide clear answers regarding validity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, it may improve the lecturer's teaching quality and, on the other hand, it may provide a wise and precise decision making tool for the administrative staff with regard to lecturers continuing employment, tenure, promotion of appointment committees and so on. Many studies have indicated strong evidence with regard to the validity and reliability of the teaching evaluation tool (Al-Saghir, 2008;Onwuegbuzie, Daniel, & Collins, 2009). On the other hand, Spooren, Brockx and Mortelmans (2013) claimed that teaching evaluation by students has thus far failed to provide clear answers regarding validity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La evaluación a los docentes por parte de los estudiantes como un instrumento para medir la efectividad de los académicos es una práctica que se ha generalizado en las universidades de todo el mundo (Kuzmanovic, Savic, Popovic, y Martic, 2013;Onwuegbuzie et al, 2009). Estas evaluaciones comenzaron a utilizarse alrededor de los años 20 (Morley, 2013), siendo su propósito original la recolección de información que sirviera para retroalimentar la práctica docente (Sproule, 2000).…”
Section: Evaluación De Las Habilidades Docentesunclassified
“…Esta importancia radica en los dos grandes propósitos para los cuales se lleva a cabo, por una parte, sus resultados son utilizados para contribuir al mejoramiento de la calidad docente (propósito formativo), y por otra parte, son un insumo para la toma de decisiones respecto a la permanencia y promoción de los académicos en las instituciones (propósito sumativo). De esta forma, se ha vuelto un requisito explícito en el sistema de evaluación de las instituciones de educación superior a nivel internacional (Kember, Leung, y Kwan, 2002), lo que conlleva la exigencia constante de mayor objetividad y precisión en su despliegue (Onwuegbuzie, Daniel, y Collins, 2009). …”
Section: Introductionunclassified
“…Measuring the student experience is assuming increasingly importance in Higher Education (hereafter, HE) representing a widespread method for evaluating teaching quality whose importance is relevant for taking the major formative and summative academic decisions (Berk, 2005;Gravestock & Gregor-Greenleaf, 2008;Onwuegbuzie et al, 2009). …”
Section: Introductionmentioning
confidence: 99%